The use of garment care labels in relation to the attitudes of some local garment manufactures - Cruz, Marlene Cheryl R.
The Philippine Bureau of Product Standards has set guidelines regardirding the use of garment care labels. Still not all local garment manufacturers use them. The objective of this study is to determine the distinct differences between local garment manufacturers who use and do not use garment care labels. The two groups of garment manufacturers were compared according to their background information and attitudes on selected factors. Background information included number of years in the business, types of products sold, and types of fibers and fabrics used. Their attitudes were compared according to their responses on the following factors: concept of garment care labels, concept of quality, importance given to consumer education, and company objectives and vision for the industry. Ten (10) local garment manufacturers without garment care labels (Group A) and ten (10) with garment care labels (Group B) participated in this study. They answered a questionnaire patterned after the Likert Scale, and data were analyzed using the t-test. The results of the study showed that there was no significant difference between the two groups of manufacturers based on the number of years in the business, types of products sold, and types of fibers and fabrics used. There was also no significant difference in their attitudes on concept of garment care labels, importance given to consumer education, and company objectives and vision for the industry. However, the two groups of local garment manufacturers were statistically different in their concept of quality. Garment manufacturers without garment care labels perceived a garment with a fashionable design and silhouette as high quality, while those with garment care labels gave more importance to performance of garments.